Information Security and Privacy 19th Australasian Conference, ACISP 2014, Wollongong, NSW, Australia, July 7-9, 2014. Proceedings - Susilo, Willy; Mu, Yi.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed conference proceedings of the 19th Australasian Conference on Information Security and Privacy, ACISP 2014, held in Wollongong, NSW, Australia, in July 2014. The 26 revised full papers and 6 short papers presented in this volume were carefully selected from 91 submissions. The papers are organized in topical sections on cryptanalysis; cryptographic protocols; fine-grain cryptographic protocols; key exchange, fundamentals, lattices and homomorphic encryption, and applications.
Cryptanalysis -- Cryptographic protocols -- Fine-grain cryptographic protocols -- Key exchange -- Fundamentals -- Lattices -- Homomorphic encryption -- Applications.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Electronic books